UKRAINIAN PEASANTRY AS AN OBJECT OF AGRARIAN REFORMS - G. G. Krivchik (Nauka ta progres transportu, 2014)
The purpose. The article attempts to analyze the agrarian policy of the modern Ukrainian State in the context of its human factor. It demonstrates the effects of agrarian reforms on social sphere of Ukrainian countryside. Methodology. The author uses the following methods: dialectical – in the depiction of the controversial nature of agrarian reforms; retrospective – in determination of the main stages of agrarian transformations inUkraine; comparative – in revealing common and different features in the agrarian policy of theUSSR and modernUkraine.The scientific novelty is in the substantiation of the natural unity of economic and social policies in agriculture, the use of a variety of historical sources for this purpose. Conclusions. While conducting agrarian reform, started in the early 1990s, and continued up to the present time, only economic factors are taken into consideration. At the same time, human factor, and the interests of the peasantry, in particular, were ignored and not taken into account, despite the declarations and promises of politicians. Peasants were removed from the determination of objectives, directions and methods of the agrarian reform. They acted solely as an object and not the subject of the reform. In this sense, the methods for carrying out agrarian reforms in an independent and democraticUkraine do not differ much from the methods of the Bolshevik leadership. Thus, as it is shown in the article, the consequences of the agrarian reform can be equally dangerous for Ukrainian peasants. The peasants will lose their land forever and become laborers on the land inherited from previous generations. While carrying out a large-scale reform of the agrarian sector, it mustn’t be allowed for oligarchs to take countryside, land and agriculture into their hands. The regulations of sale and purchase of the land must be so that the Ukrainian peasant will remain the main contractor.